Implementation of a decision support system in the selection of scientific articles using the weighted product method at the rumah jurnal larisma - Elfida Putri Handayani Nasution (Lembaga Riset Mutiara Akbar, 2026)
The increasing number of scientific articles submitted to journals demands an objective, consistent, and efficient selection process. Manual selection processes involving multiple criteria have the potential to create subjectivity and slow down editorial decision-making. This study aims to implement a Decision Support System in the selection of scientific articles using the Weighted Product method at LARISMA Journal House. This study uses a quantitative approach with fifteen articles as alternative decisions assessed based on five criteria: scope suitability, research novelty, methodological clarity, writing structure, and reference quality. The weight of the criteria is determined based on the journal manager's priorities. The results show that the Weighted Product method is able to produce an objective and measurable article ranking, thus assisting editors in determining the priority of articles worthy of further processing. The implementation of this decision support system has been proven to improve the efficiency, objectivity, and consistency of editorial decision-making in the management of scientific journals.